2022
DOI: 10.1155/2022/3726423
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, Practices, and Associated Factor towards Hepatitis B Virus Infection among Health Care Professionals at Tibebe Ghion Specialized Hospital, Bahir Dar, Northwest Ethiopia, 2021: A Cross Sectional Study

Abstract: Background. Hepatitis B virus (HBV) infection is the major infectious hazard for health care personnel. The global prevalence of HBV infection is highly heterogeneous, and the highest prevalence (6.2 and 6.1%) is among the World Health Organization Western Pacific and World Health Organization African regions, respectively. The pooled prevalence of HBV in Ethiopia among health workers was accounted for 5%. The prevalence rate of HBV in health care workers is about 2–10 times higher than the general population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…In this study, some participants had misconceptions about the mode of transmission and treatment options available for pregnant women with HBV. These findings agree with other studies that reported unsatisfactory knowledge of HBV among healthcare personnel ( Adjei et al, 2022 ; Belete et al, 2022 ; Chen et al, 2018 ; Freeman, Chea & Shobayo, 2023 ). Specifically, some of the participants believed that sweat was a medium for the transmission of HBV, contrary to what was reported by Schillie et al (2018) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, some participants had misconceptions about the mode of transmission and treatment options available for pregnant women with HBV. These findings agree with other studies that reported unsatisfactory knowledge of HBV among healthcare personnel ( Adjei et al, 2022 ; Belete et al, 2022 ; Chen et al, 2018 ; Freeman, Chea & Shobayo, 2023 ). Specifically, some of the participants believed that sweat was a medium for the transmission of HBV, contrary to what was reported by Schillie et al (2018) .…”
Section: Discussionsupporting
confidence: 93%
“…At the healthcare worker level, studies have reported unsatisfactory knowledge of HBV and its transmission and treatment options for infected pregnant women ( Adjei, Nachinab, Atibila, Ansah-Nyarko, Kyei & Fosu, 2022 ; Belete, Wondale, Kiros & Demissie, 2022 ; Freeman, Chea & Shobayo, 2023 ). The unsatisfactory knowledge and lack of awareness have largely been attributed to a lack of training and continuous education for healthcare personnel, who are major stakeholders in the PMTCT program ( Moturi et al, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Overall, 38.3% of respondents had a positive attitude toward HBV infection, while 61.7% had a negative attitude. This result is lower than those of studies conducted in Bahirdar, Ethiopia (40.3% positive, 59.7% negative) (20), Gondar, Ethiopia (43.8% positive, 56.2% negative) (35), and Jordan (40% positive, 60% negative) (36). The differences may be due to the study participants; this study involved HBV-infected individuals, while the other studies involved health professionals who generally have a better attitude toward the virus.…”
Section: Discussionmentioning
confidence: 55%
“…The mean knowledge level was 31%, with half of the participants scoring below the mean (poor knowledge) and the other half above the mean (good knowledge). This result contrasts with studies in Bahirdar, Ethiopia, where 65.6% had good knowledge and 34.4% had poor knowledge (20), and in Northwest Ethiopia, where 80% had good knowledge and 20% had poor knowledge (19). In Khartoum, Sudan, 58% knew about HBV (33).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation